Stellar mass spectrum within massive collapsing clumps - Lee, Yueh-Ning; Hennebelle, Patrick (Astronomy and astrophysics (Berlin), 2019)
Context. The stellar mass spectrum is an important property of the stellar cluster and a fundamental quantity to understand our Universe. The fragmentation of diffuse molecular cloud into stars is subject to physical processes such as gravity, turbulence, thermal pressure, and magnetic field. Aims. The final mass of a star is believed to be a combined outcome of a virially unstable reservoir and subsequent accretion. We aim to clarify the roles of different supporting energies, notably the thermal pressure and magnetic field, in determining the stellar mass. Methods. Following our previous studies, we performed a series of numerical experiments of stellar cluster formation inside an isolated molecular clump. We investigated whether any characteristic mass is introduced into the fragmentation processes by changing the effective equation of state (EOS) of the diffuse gas, that is to say gas whose density is below the critical density at which dust becomes opaque to its radiation, and the strength of the magnetic field. Results. The EOS of the diffuse gas, including the bulk temperature and polytropic index, does not significantly affect the shape of the stellar mass spectrum. The presence of magnetic field slightly modifies the shape of the mass spectrum only when extreme values are applied. Conclusions. This study confirms that the peak of the initial mass function is primarily determined by the adiabatic high-density end of the EOS that mimics the radiation inside the high-density gas. Furthermore, the shape of the mass spectrum is mostly sensitive to the density PDF and the magnetic field likely only a secondary role. In particular, we stress that the Jeans mass at the mean cloud density and at the critical density are not responsible for setting the peak.